Information technology. International standardized profile TAnnnn. Connection-mode transport service over connectionless-mode network service. MAC, PHY and PMD sublayer dependent and Station Management requirements over an FDDI LAN subnetwork Part 14, (15th December 1995) - British Standards Institution,
No abstract available